Vaginohisteroscopía en consultorio: histeroscopio de Bettocchi nueva técnica de diagnóstico y tratamiento ginecológico - Carvajal M., Antonio; Pérez M., Claudio; Miranda V. , Cristián; Carvajal A., Nicolás (Revista Hospital Clínico Universidad de Chile, 2008)
The global trend in surgical procedures is to be as least invasive as possible, causing minor injury to tissues, to reduce the days of hospitalization, to minimize post-operative pain and an early work reintegration. With endoscopy this has achieved and particularly with the hysteroscopy, which is a surgical procedure that allows you to visualize the uterine cavity, to diagnose and resolve the pathologies. The use of the Bettocchi hysteroscope, has revolutionized the gynecological diagnosis and treatment, because it is an ambulatory procedure, without hospitalization nor use of anesthesia. This article aims to describe this technique, its indications and contraindications